Understanding Readiness and Motivation for Digital Mental Health Support - Jardine, Jacinta (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2025)
Psychological therapy is an effective and acceptable form of care for distress, however, there is a vast disparity between the number of people who are suffering and those receiving support. Digital mental health interventions (DMHIs) have been developed as a way to address this escalating care gap, providing accessible, scalable, and immediately available support. When accompanied by human guidance, DMHIs show consistent clinical effectiveness in improving client outcomes. However, while they are being successfully implemented in many real-world settings, low client uptake and engagement rates are seen as an issue undermining the potential reach and utility of these interventions. A lack of readiness or motivation for DMHIs has been proposed as a core client factor leading to low uptake and engagement. There are a wide range of frameworks and models currently being used to understand readiness and motivation for digital mental health support, however none of these have been developed specifically for this unique context. There is also a dearth of research directly with clients who have difficulties engaging with DMHIs, as they are inherently hard to reach. Despite these significant gaps in our knowledge and theory, digital interventions and strategies aimed at increasing client readiness and motivation have been developed and deployed as a means of tackling the engagement problem. It is unclear how effective these interventions are and if this is where design efforts should be directed when addressing low uptake and engagement with DMHIs. This thesis examines the role of readiness and motivation in relation to uptake and engagement with digital mental health support. First, it contributes to our knowledge on how readiness and motivation are framed in terms of existing theory and research practice. It then explores the landscape of digital interventions aimed at enhancing client readiness for therapy, to outline the current practices being used and their feasibility. Findings from this review indicated that while digital readiness interventions do show potential as a means of increasing uptake and engagement with therapy, there are risks involved (e.g., a potential decline in engagement or outcomes). Thus, further in-depth research is needed to deepen our understanding of this space before additional design efforts can be made. This thesis then presents an observational, mixed-methods inquiry into the barriers that prevent uptake and early engagement with DMHIs. The aim of this study was to understand the lived experiences of real, non-engaging clients from a broad, context aware perspective; hence the study was conducted across four different healthcare ecosystems in the UK and US. Findings revealed that client needs and motivation for mental health support are multifaceted, fluctuating and impacted by contextual factors and self-stigma. The problem of low uptake and engagement with DMHIs can therefore be addressed by reconsidering the design, context, framing, delivery and goals of these interventions. Building on these findings, this thesis finally describes a complementary, temporal analysis of the interview data from the previous study. This analysis explored the mental health journeys of individual participants, examining the role of readiness and motivation in more detail and incorporating service-level perspectives from four expert stakeholders. Findings indicated that when it comes to DMHIs, motivation is a more useful construct than readiness because it more adequately represents the nuanced, contextual instances wherein clients decide or are driven to engage. Furthermore, this study indicated that low engagement with DMHIs is not necessarily a problem when viewed from the long-term, system-level perspective of ongoing client mental health journeys. This thesis enriches the HCI field with a better understanding of readiness and motivation for digital mental health support, as well as shedding light on the issue of low client uptake and engagement more broadly. Hence, this thesis helps those researching and designing DMHIs to make more informed decisions when navigating this complex design space.
APPROVED
Keywords: uptake; digital mental health interventions; online therapy; motivation; readiness; stages of change; engagement